2018
DOI: 10.1532/hsf.1947
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dilatation and Posterior Papillary Muscle Displacement in an Ex Vivo Pulsatile Model of Functional Mitral Regurgitation

Abstract: Background: Surgical method of choice for functional mitral regurgitation (FMR) is debatable, since recurrence of FMR post-annuloplasty has been reported in a significant number of cases. Developing a pulsatile FMR heart model by left ventricular dilatation can be a favorable option for usage in the primary stages of developing new surgical techniques that adjunctively targets the posterior papillary muscle (PPM) geometry.Methods: PPM of ex vivo ovine hearts (N = 22) was displaced by three different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Moreover, achieving sufficient dilation of healthy heart samples, especially hypertrophic swine hearts, is often difficult when used as a whole heart with all the supporting tissues remained [ 15 ]. Several previous studies have reported FMR production [ 9 , 12 , 14–16 ]; however, none of them produced sufficient MR that fulfils the interventional indication. Jaworek et al [ 13 ] produced an FMR model by dilating the annulus and LV by pressurizing the LV with a continuous flow pump after clamping the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, achieving sufficient dilation of healthy heart samples, especially hypertrophic swine hearts, is often difficult when used as a whole heart with all the supporting tissues remained [ 15 ]. Several previous studies have reported FMR production [ 9 , 12 , 14–16 ]; however, none of them produced sufficient MR that fulfils the interventional indication. Jaworek et al [ 13 ] produced an FMR model by dilating the annulus and LV by pressurizing the LV with a continuous flow pump after clamping the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The LV wall around the PPM was sutured closed with a 3 cm diaphragmatic patch; this creates a focal dilation of the LV wall and cause outward displacement of the PPM. Kradangnga et al [Kradangnga 2018] studied the ex vivo pulsatile heart model of functional mitral regurgitation and showed that the 3 cm crescent-shaped diaphragmatic patch size placement induced the highest heart models with MR and also produced the highest MR volume. From this data, the 3 cm patch was used to increase the length of the LV wall at the level of the PPM.…”
Section: Methodsmentioning
confidence: 99%
“…Six intracardiac 2 mm piezo-electric crystals (2 mm round piezo-electric crystals, Sonometrics, London, Canada) were sutured to 6 mitral apparatus landmarks as illustrated in the Kradangnga et al study [Kradangnga 2018]. Nine crystal pairs were of interest and used for the LVV calculation and analysis of the annular and papillary muscles geometry (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation